Giant surfactant-stabilized N2-foam for enhanced oil recovery after water flooding. Issue 54 (4th October 2019) - Bai, Yongqing; He, Shaoqun; Lian, Yue; Dai, Caili; Zhang, Huaihao
Abstract : A giant surfactant with high surface activity and strong viscosifying ability was prepared through a facile one-pot procedure for foam stabilization in EOR projects. Abstract : A novel giant surfactant, APOSS-PS50, possessing good surface activity, and viscosifying and reinforcing ability as a foam stabilizer, was synthesized successfully to enhance the physical properties of foaming solutions and foam. APOSS-PS50 was widely distributed at the foam gas–liquid interface and adjacent liquid layers through diffusion and adsorption, obviously decreasing the surface tension and improving the foamability and stability of the foam. Furthermore, the aggregation of APOSS-PS50 in the foam films resulted in the formation of a self-assembled nano-sized network through supramolecular interactions (such as hydrogen bonding, π–π stacking, and van der Waals attraction), thus increasing the foam viscoelasticity, including its interfacial viscoelastic modulus and apparent viscosity. Meanwhile, from the sandpack flooding experiments, compared with HPAM/AOS (HPAM: partially hydrolyzed acrylamide and AOS: alpha olefin sulfonate), the differential pressure and final oil recovery after APOSS-PS50 /AOS foam flooding increased by 23.5% and 23.2%, up to 2.68 MPa and 81.7%, respectively. In general, APOSS-PS50 significantly promoted the plugging, profile control and oil displacement performance of foam.